Is yoga a suitable treatment for rheumatoid arthritis: current opinion - Telles S; Singh N (Dove Medical Press, 2012)
Shirley Telles, Nilkamal SinghPatanjali Research Foundation, Haridwar, IndiaAbstract: We reviewed published literature regarding the use of yoga for managing rheumatoid arthritis to determine whether adequate evidence exists to suggest its usefulness as a therapy. A search for previous studies involving yoga and rheumatoid arthritis in PubMed yielded eight reports. These studies reported the benefits of yoga in the physical and mental health of patients with rheumatoid arthritis (RA), suggesting that yoga is a useful add-on therapy for RA patients. However, all studies showed limitations with respect to sample size, study design, description and duration of yoga intervention, and assessment tools and statistical methods used. Additionally, the studies did not attempt to understand the mechanisms underlying observed benefits. Hence, evidence suggests a definite role of yoga in RA improvement, reducing pain, improving function, and creating a positive mental state. However, detailed analysis and additional studies are necessary to verify these observations.Keywords: bibliographic database search, PubMed, rheumatoid arthritis, yoga